Molecular and epidemiological analysis of Babesiosis by Babesia bigemina in cattle from the Giron Municipality, Azuay, Ecuador - Bustamante–Ordóñez, Jorge Gualberto; Bustamante–Guzmán, Diego Andrés; Rivera-Pirela, Sergio Emiro (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Babesiosis is a disease caused by an intraerythrocytic protozoan Phylum Apicomplexa, class Sporozoea, subclass Piroplasmea, superfamily Babesioidea, family Babesidae, genus Babesia within which the species Babesia bovis and B. bigemina in cattle stand out. It occurs in the tropics and subtropics of the World and is transmitted mainly by Rhipicephalus microplus ticks. Whole blood samples were analyzed using Giemsa stained blood smears, conventional PCR to detect, from the DNA in variable regions of the 18S rRNA gene, the 393 bp band corresponding to B. bigemina, then subjected to the restriction enzyme Alu. I (5’AG↓CT3’ recognition sequence), capable of cutting the ribosomal DNA amplicon of B. bigemina, generating three fragments of 38, 144 and 211 bp. For qPCR–RT amplification, the B. bigemina–specific Primer design qPCR kit was used. By jugular vein puncture, 100 samples of bovines belonging to the Agricultural Production Units (UPA) of two geomorphological levels less-than 2,200 masl (low) and greater-than 2,200 masl (high) were obtained, Girón Municipality, inter–Andean alley of the Republic from Ecuador with Holstein and Criollo Mestizo cattle that produce milk. The R. microplus tick was detected in 100% of the animals evaluated. With epidemiological surveys, different local risk factors associated with bovine babesiosis were analyzed, according to the results obtained with each of the techniques. Using blood smears, 16 of samples positive for B. bigemina were identified, 7.54% in low and 25.53% in high. By PCR–RFLP 11 with 9.43% low and 12.76% high. The qPCR–RT showed a higher prevalence of 43% of B. bigemina with 54.72% low and 29.79% high. Altitude was significantly associated with parasitemia in high areas according to the Giemsa–stained smear technique. Different results were obtained with the qPCR kit, which revealed higher parasitemia in low–lying areas, with low vector load, tick–killing baths less-than 60 days, and in the winter season, when the presence of B. bigemina increased significantly.